2014
DOI: 10.1021/jf501155n
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Metabolic Impacts of a Defatted Green Marine Microalgal (Desmodesmus sp.) Biomass in Diets for Weanling Pigs and Broiler Chickens

Abstract: Two experiments were conducted to determine the nutritional and metabolic impacts of defatted green microalgal (Desmodesmus sp.) biomass (DGM), protease, and nonstarch polysaccharide degrading enzymes (NSPase) in diets for weanling pigs and broiler chicks. Pigs fed 10% DGM for 28 days had growth performance comparable to the controls, but 23-39% lower (P < 0.05) plasma urea nitrogen concentrations. Broilers fed 15% DGM had 16% greater (P < 0.05) gain/feed efficiency than the control (0.78 vs 0.67) over the 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In the food producing pathways, food products are assumed to be perfectly substitutable for corn and oil crops in GCAM, based upon the results of animal feed trials (Drewery et al 2014, Ekmay et al 2014, Kiron et al 2016. The fuel producing pathways model the thermochemical conversion via hydrothermal liquefaction (Jones et al 2014) (FL) or wet extraction (Beal et al 2011) (FD+FL) of algal biomass to yield lipids which are subsequently upgraded to green diesel fuel via a hydrotreatment process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the food producing pathways, food products are assumed to be perfectly substitutable for corn and oil crops in GCAM, based upon the results of animal feed trials (Drewery et al 2014, Ekmay et al 2014, Kiron et al 2016. The fuel producing pathways model the thermochemical conversion via hydrothermal liquefaction (Jones et al 2014) (FL) or wet extraction (Beal et al 2011) (FD+FL) of algal biomass to yield lipids which are subsequently upgraded to green diesel fuel via a hydrotreatment process.…”
Section: Methodsmentioning
confidence: 99%
“…The use of algal biomass as a source of animal or human food offers an alternative revenue stream and additional avenues for reducing emissions and other environmental impacts. Animal feed trials have demonstrated that whole and defatted algal biomass can substitute a significant portion of both corn and soy in the diets of cattle, pigs, chicken and salmon (Drewery et al 2014, Ekmay et al 2014, Kiron et al 2016 (and additional research summarized in the SI). Further nutritional research and product development will be necessary before algal food products are widely adopted in animal and human diets.…”
Section: Introductionmentioning
confidence: 99%
“…Evans, et al [14] incorporated 16% microalgae into broiler starter diets and did not find any performance detriment. Ekmay, et al [15] found weanling pigs and broiler chicks performed well with dietary inclusion of 10% and 15% defatted green microalgal biomass, respectively. Utilization of microalgae in aquaculture is another growing market, and they can be used directly in aquaculture feeds [11].…”
Section: Introductionmentioning
confidence: 99%
“…While no differences were noted when the microalgae was fed at 7.5%, when inclusion increased to 15% this resulted in decreased feed intake, decreased egg production and decreased efficiency of feed utilization. However, Ekmay et al (2014) reported that when 15% of a defatted green microalgal biomass (Desmodesmus sp. ; Cellna, Kailua-Kona, HI) replaced a corn-soybean meal diet broilers had a 16% greater feed efficiency than their control-fed counterparts over a 42 day period.…”
Section: Microalgae In Animal Nutritionmentioning
confidence: 99%
“…Research with a defatted green microalgal biomass (Desmodesmus sp. ; Cellna, Kailua-Kona, HI) fed to replace 10% of a corn-soybean meal diet in weanling Yorkshire × Hampshire × Landrace pigs (n = 32) showed no difference in overall growth performance; however, over the 42 d feeding period the algae fed pigs had 23-39% lesser plasma urea nitrogen concentrations (Ekmay et al, 2014). Isaacs et al (2011) directly replaced soybean meal in the diets of 27 weanling pigs (BW = 10.69 ± 0.22 kg) with either 6.6% of a whole fat diatom microalgae (Staurosira spp.)…”
Section: Microalgae In Animal Nutritionmentioning
confidence: 99%